Bottom-up and top-down effects of browning and warming on shallow lake food webs - Rivera Vasconcelos, Francisco (2019)
Productivity and trophic structure of aquatic ecosystems result from a complex interplay of19 bottom-up and top-down forces that operate across benthic and pelagic food web compartments.20 Projected global changes urge the question how this interplay will be affected by browning21 (increasing input of terrestrial dissolved organic matter), nutrient enrichment and warming. We22 explored this with a process-based model of a shallow lake food web consisting of benthic and23 pelagic components (abiotic resources, primary producers, grazers, carnivores), and compared24 model expectations with the results of a browning and warming experiment in nutrient-poor25 ponds harboring a boreal lake community. Under low nutrient conditions, the model makes three26 major predictions. (1) Browning reduces light and increases nutrient supply; this decreases27 benthic and increases pelagic production, gradually shifting productivity from the benthic to the28 pelagic habitat. (2) Because of active habitat choice, fish exert top-down control on grazers and29 benefit primary producers primarily in the more productive of the two habitats. (3) Warming30 relaxes top-down control of grazers by fish and decreases primary producer biomass, but effects31 of warming are generally small compared to effects of browning and nutrient supply.32 Experimental results were consistent with most model predictions for browning: light penetration,33 benthic algal production, and zoobenthos biomass decreased, and pelagic nutrients and pelagic34 algal production increased with browning. Also consistent with expectations, warming had35 negative effects on benthic and pelagic algal biomass and weak effects on algal production and36 zoobenthos and zooplankton biomass. Inconsistent with expectations, browning had no effect on37 zooplankton and warming effects on fish depended on browning. The model is applicable also to38 nutrient-rich systems, and we propose that it is a useful tool for the exploration of the39 consequences of different climate change scenarios for productivity and food web dynamics in40 shallow lakes, the worldwide most common lake type.